A formação do professor de Arte na modalidade educação a distância /EAD/UAB/UFES - Simões, Vera Lúcia de Oliveira (2013)
This thesis is the result of a research configured as a case study, with the purpose of identifying in the course of Visual Arts/UAB/UFES: conceptions of Art teacher that guide/base the semi-presential Visual Arts Course and how they manifest in the curriculum of the course, in official documents which set the standards and discourses and practices proposed by teachers and instructors; the conception that underlies the formation of Distance Education (DE) Art teacher; concepts that underlie the DE legislation/standards on the teaching of art; discourse and practices of teacher-trainers present in educational materials offered on the Moodle platform; the modes of interaction between teacher and tutor, teachers and students, students and tutors and between presential and at distance tutors. The research is supported by the bakhtinian referential analysis of verbal interactions and the construction of discourses and knowledge. Therefore, the methodological approach is grounded in the theoretical assumptions of Mikhail Bakhtin, with emphasis on the concept of dialogism, understood here as the relationship that exists between the discourses and thus between self and other, and the concept of polyphony considering the plurality of voices that coexist and interact in the discursive practices of those who inhabit a Virtual Learning Environment (VLE). Faced with a universe consisting of 44 subjects distributed in all three axes –- General and Pedagogical Training, Specific Training and Practice of Art Teaching –- which structure the course, there was the need for a breakdown and analysis was performed in the disciplines: Research Internship I, Art History III and Video being each of these components of a particular axis. As expected this virtual environment identified a multitude of voices present in the statements that constitute the writings on the DL; legislation governing teacher training, course design, the structure of the curriculum, specialist teachers' practices, mentoring interventions, the interaction of students. As it is a profusion of voices coming from different subjects and interaction, it could not be different, and therefore several conceptions of art teacher are present, sometimes perceived in the practices and discourses of the same subject. This research confirms the Bakhtinian theory that the borders of interaction between self and other, the relationship between subjects and the subjects with society that constitute the discourses are constructed and the meaning of the text. Even when the interaction is not as explicit or obvious, it is from the theory that subjects are constituted and show their inventiveness, and become responsible or "answerable" for their activities considering the specific time and place each occupies in the world.